Antimicrobial and anti-biofilm activity of essential oils extracted from Clausena lansium (Lour.) Skeels and their main constituents against Streptococcus mutans - Wu, Zibei; Zhang, Xufeng; Wang, Lili; Sui, Jinlei; Yu, Mingqi; Bao, Bingzhangke; Qian, Jianing; Yi, Guohui; Ma, Yinzheng; He, Xiaowen (Frontiers in Microbiology, 2025)
Streptococcus mutans is one of the most significant pathogens leading to dental caries by producing highly cariogenic biofilms within the oral cavity. However, the increasing antimicrobial resistance brings great difficulties to the prevention and treatment of dental caries. Therefore, it is very important to develop new and effective antimicrobial agents from natural sources. Clausena lansium (Lour.) Skeels, a plant commonly cultivated in Southern China, is rich in various active constituents. In this study, the main constituents of the essential oils extracted from Clausena lansium leaves (EOL), seeds (EOS), peels (EOP) were precisely analyzed by gas chromatography–mass spectrometry. The antimicrobial and anti-biofilm activities of EOL, EOS, and EOP, along with their main chemical constituents, against Streptococcus mutans were comprehensively evaluated. The primary constituent in EOL was β-caryophyllene, with a content of 112.29 mg/mL. EOS was found to be abundant in sabinene and 4-terpineol, with constituents of 147.21 mg/mL and 54.36 mg/mL, respectively. In EOP, the most predominant constituent was β-phellandrene, with a content of 173.95 mg/mL. The minimum inhibitory concentrations of EOL, EOS, and EOP were 0.12, 2.00, and 1.00 mg/mL, respectively. The minimum concentrations of inhibiting at least 90% biofilm formation of EOL, EOS, and EOP was 0.12 mg/mL, 2.00, and 2.00 mg/mL, respectively. Intriguingly, the antimicrobial and anti-biofilm efficacies of the main constituents were significantly lower than those of the essential oils. By observing the dynamic changes of the biofilm formation of S. mutans treated with essential oils, it was found that the process of biofilm formation was greatly delayed. In some cases, there was even no biofilm formation. The results of real-time quantitative PCR indicated that the expression levels of brpA, gtfB, gtfC, gtfD, and luxS genes were down-regulated after treatment with the essential oils. This study reinforces the potential of Clausena lansium as a promising source for developing new antimicrobial and anti-biofilm agents. They could inhibit the proliferation and virulence of S. mutans, thereby contributing to the control of dental caries.